Why do OECD-Countries trade more? - Henri L.F. de Groot; Gert-Jan Linders; Piet Rietveld (Tinbergen Institute, 2003)
Ineffective institutions increase transaction costs and reduce trade. This paper shows that differences in the effectiveness of institutions offer an explanation for the tendency of OECD countries to trade disproportionately with each other, and with non-OECD countries.
Keywords: F14; F15; 330; bilateral trade; gravity model; institutions; OECD; Intraindustrieller Handel; Institutionelle Infrastruktur; Handelseffekt; Gravitationsmodell; OECD-Staaten